2018
DOI: 10.1056/nejmoa1810171
|View full text |Cite
|
Sign up to set email alerts
|

Brigatinib versus Crizotinib in ALK-Positive Non–Small-Cell Lung Cancer

Abstract: BACKGROUNDBrigatinib, a next-generation anaplastic lymphoma kinase (ALK) inhibitor, has robust efficacy in patients with ALK-positive non-small-cell lung cancer (NSCLC) that is refractory to crizotinib. The efficacy of brigatinib, as compared with crizotinib, in patients with advanced ALK-positive NSCLC who have not previously received an ALK inhibitor is unclear. METHODSIn an open-label, phase 3 trial, we randomly assigned, in a 1:1 ratio, patients with advanced ALK-positive NSCLC who had not previously recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
644
0
38

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 797 publications
(746 citation statements)
references
References 31 publications
18
644
0
38
Order By: Relevance
“…In phase I/II trials in crizotinib resistance ALK‐positive NSCLC patients, brigatinib showed 72% overall response with a median PFS of 11–13 months . A recently published phase III trial showed a superior efficacy of brigatinib as compared with crizotinib in the treatment‐naïve ALK‐fusion positive NSCLC, with an estimated 12‐month event‐free survival of 67% . The predominant resistance mutation seen in response to alectinib therapy is ALK‐G1202R which is resistant to most ALK TKIs, with the exception of lorlatinib (see below).…”
Section: Targeting Alkmentioning
confidence: 99%
“…In phase I/II trials in crizotinib resistance ALK‐positive NSCLC patients, brigatinib showed 72% overall response with a median PFS of 11–13 months . A recently published phase III trial showed a superior efficacy of brigatinib as compared with crizotinib in the treatment‐naïve ALK‐fusion positive NSCLC, with an estimated 12‐month event‐free survival of 67% . The predominant resistance mutation seen in response to alectinib therapy is ALK‐G1202R which is resistant to most ALK TKIs, with the exception of lorlatinib (see below).…”
Section: Targeting Alkmentioning
confidence: 99%
“…Birinci basamakta alektinib, brigatinib ve ceritinib, crizotinib veya kemoterapiye göre üstünlüğü gösterilmiş diğer ajanlardır. (9)(10)(11). Crizotinib altında progresyon gösteren hastalarda ise benzer şekilde alektinib, ceritinib, brigatinib ve lorlatinib kemoterapiye karşı etkinlikleri gösterilmiş ajanlardır.…”
Section: Introductionunclassified
“…1 More recently, a phase 3 trial in crizotinib-naive patients with ALK-positive NSCLC showed that progression-free survival was significantly longer among patients who received brigatinib than among those who received crizotinib (12-month progression-free survival, 67% versus 43%; hazard ratio, 0.49 [95%CI, 0.33-0.74]; P < .001). 2 The recommended dose of brigatinib is 90 mg orally once daily for the first 7 days of treatment, which, if tolerated, is followed by escalation to 180 mg once daily. Brigatinib single-and repeat-dose systemic exposures increased dose-proportionally following administration in patients with cancer across the dose range of 60-240 mg once daily.…”
mentioning
confidence: 99%